PENGEMBANGAN MEDIA PEMBELAJARAN CROSSWORD PUZZLE BERBASIS ANDROID PADA MATERI ORGAN PERNAPASAN MAKHLUK HIDUP - zakiyatul mu'arofah (Universitas Muhammadiyah Purwokerto, 2022)
The purpose of this study is (1) to determine the level of analysis of the need for developing Android-based crossword puzzle media on learning natural science of breathing apparatus living things in Madrasah Ibtidaiyyah throughout Tembarak and Selopampang Districts; (2) to find out the feasibility test of developing Android-based Crossword media on respirator material for students; and (3) to find out the effectiveness of developing android-based crossword puzzle media on the science of breathing organisms for MI Nurul Ummah Tawangsari Tembarak sub-district students. This research method is research and development (R&D) with ADDIE procedures (Analysis, Design, Development, Implementation, and Evaluation) with research subjects being teachers and students of Madrasah Ibtidaiyyah Nurul Ummah Tawangsari. The research instruments used were real condition questionnaires, needs analysis questionnaires, interview guidelines, pretest and posttest question instruments as well as individual, group, and limited trial sheets. The stages of R&D are as follows: 1) a preliminary study; 2) the development of crossword puzzle media; 3) product effectiveness testing. The results showed as follows: (1) the need for innovative learning media is needed in science learning (2) the form of crossword puzzle media development containing human and animal respiratory organs material implemented in game applications on android, the validation test of crossword puzzles was tested based on items - bullet validation sheet material expert questions, the average score obtained is 81% while the validation test based on the validation sheet media experts got an average of 91%, an individual trial averaged 95.69%, a group test of 95%, a limited group trial gained a score of 95.38%. From these results it can be concluded that the crossword puzzle media is feasible to be used 3) the effectiveness test of the crossword puzzle media with a t test value of 11,159.